The Role of English Language Teaching in Facilitating International Communication and Collaboration - Rifial Rifandi (Universitas Muhammadiyah Makassar, 2025)
This study explores the role of digital tools in enhancing international collaboration and improving language teaching within higher education. Focusing on the integration of technology in language education, the study aims to assess its impact on student engagement and learning outcomes. A mixed-methods approach was used, including surveys and interviews with educators and students who participated in virtual collaborative projects. The findings indicate that digital tools, such as video conferencing and online collaboration platforms, significantly improve communication across diverse cultural backgrounds. Participants reported increased motivation, engagement, and improvement in language skills due to these collaborative experiences. Additionally, the study underscores the role of English as a common language in facilitating interdisciplinary learning. In conclusion, the research highlights the importance of integrating digital strategies into teaching practices to enhance collaboration and language acquisition. Recommendations include the development of structured virtual exchange programs and the incorporation of digital tools into curricula to better prepare students for a globalized workforce.